ASPEK HUKUM PENGALIHAN PIUTANG ATAS NAMA (CESSIE) KARENA WANPRESTASI PT. BANK SRI PARTHA KEPADA PT. SRI PARTHA PUSAKA DENPASAR - Partha Suwirya, Ida Bagus Gede; Puspawati, I Gst. Ayu; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum, 2013)
In practice there has been a transfer agreement receivable by PT. BankSri Parthato PT. Sri Partha Pusaka, in this case, the receivables transfer from theold lenders to the new lender are moving in different fields. PT. Bank Sri Parthain this case as old creditor moving in banking and PT. Sri Partha Pusaka in thiscase as the new lender who is not moving in banking. Based on the facts thatoccurred in the field, there has been a receivables transfer agreement of theparties engaged in banking to party which is not engaged in banking. Because ofdifferences between the two parties in the receivables transfer agreement, it willlead to legal consequences inside. Therefore, I am willing to research and learnmore about the legal consequences arising following the legal aspects applicableto the receivables transfer agreement by lifting the title "LEGAL ASSIGNMENTDUE ON BEHALF (CESSIE) BECAUSE OF PT. BANK SRI PARTHA’SDEFAULTto PT. SRI PARTHA PUSAKA ".
Keywords: Legal Aspects, of Transfer of ReceivablesIn the Name(Cessie), Default